ANALISIS YURIDIS TERHADAP TINDAKAN PEMBERHENTIAN DENGAN HORMAT PADA ANGGOTA POLRI (ANALISIS PUTUSAN PENGADILAN TATA USAHA NEGARA MEDAN NOMOR 52/G.TUN/2005/PTUN-MDN) - Anderson Sirongoringo Sirongoringo; Budiman Ginting Ginting; Pendastaren Tarigan Tarigan; Jelly Leviza (USU LAW JOURNAL, 2015)
ABSTRACT The regulation on the discharge of police officers is stipulated in Law No. 2/2002 on the Republic of Indonesia State Police and on PP (Government Regulation) No. 1/2003 on the Discharge of Police Officers. The legal enforcement in the case No. 52/G.TUN/2005/PTUN-MDN has been in line with the provision of the prevailing law of procedure. The obstacle faced by judges in executing the Ruling No. 52/G.TUN/2005/PTUN-MDN is caused by the legal provisions which do not firmly regulate the enforcement of execution of the Ruling of the State Administrative Court, the absence of enforcement institution as the executor of the ruling, and the absence of sanction on the non-compliance to the ruling. Plaintiffs’ obstacle in executing the ruling is also related to the absence of a firm regulation in Law No. 2/2002 and in PP No. 1/2003 related to the court’s ruling on discharge. Keywords: Honorable Discharge, Police Officers, Ruling of the State Administrative Court